LIMITED GENDER KNOWLEDGE OF ELEMENTARY SCHOOL’S TEACHERS :A CASE STUDY OF 20 TEACHERS OF SDN 28 DAN 43 RAWANG TIMUR PADANG, WEST SUMATERA - Selinaswati Selinaswati (HUMANISMA : Journal of Gender Studies, 2018)
This research aims to describe the lack of gender knowledge of 20 teachers in two primary schools in Padang. It is assumed that teachers in primary schools are important to have gender knowledge. This is because primary schools is the basic education for pupils in building their character and constructing their mindset, especially mindset with gender awareness and gender sensitivity attitude. Thus teachers without gender bias and lack of gender knowledge plays an important role for widely spread the gender sensitivity and gender awareness in order to fight the bias gender and discrimination against women.   The research takes qualitative method by using in-depth interview and distribute questioner toward 20 teachers in 2 primary schools. The result showed that most teacher in these two primary schools have lack of knowledge about gender concept and kind of difficult to make different among the definition of sex  and gender concept. This lack of knowledge to some extent affected the learning process with several gender biases in facing their pupils in the school activities. It is recommended in increasing the socialization process of gender knowledge around primary school’s teachers.Penelitian ini bertujuan untuk mendeskripsikan kurangnya pengetahuan gender dari 20 guru di dua sekolah dasar di Padang. Diasumsikan bahwa guru di sekolah dasar penting untuk memiliki pengetahuan gender. Ini karena sekolah dasar adalah pendidikan dasar bagi siswa dalam membangun karakter mereka dan membangun pola pikir mereka, terutama pola pikir dengan kesadaran gender dan sikap sensitivitas gender. Jadi guru tanpa bias gender dan kurangnya pengetahuan gender memainkan peran penting untuk menyebarkan kepekaan gender dan kesadaran gender secara luas untuk melawan bias gender dan diskriminasi terhadap perempuan. Penelitian ini menggunakan metode kualitatif dengan menggunakan wawancara mendalam dan mendistribusikan kuesioner kepada 20 guru di 2 sekolah dasar. Hasil penelitian menunjukkan bahwa sebagian besar guru di kedua sekolah dasar ini kurang memiliki pengetahuan tentang konsep gender dan agak sulit untuk membedakan antara definisi jenis kelamin dan konsep gender. Kurangnya pengetahuan sampai batas tertentu mempengaruhi proses pembelajaran dengan beberapa bias gender dalam menghadapi murid-murid mereka dalam kegiatan sekolah. Disarankan dalam meningkatkan proses sosialisasi pengetahuan gender di sekitar guru sekolah dasar.Keyword: Gender, knowledge, elementary school.